Creating an enabling environment for research impact (REACH Discussion document) - Charles, K; Grasham, C; Hope, R; Sneddon, S; Nileshwar, A; Flint-O'Kane, M; Dreibelbis, R; Alam, MM; Flynn, C; Goyol, K; Lewis, A; Mwatsama, M; et al. (University of Oxford, 2024)
Research should benefit society: that is widely accepted. There has been much written on how to design research to deliver impact through equitable partnerships, co-production, and more. However, there has been less reflection on the enabling environment that funders and universities create to support research to have impact. In this brief we explore the experiences of creating impact through research in international development, and the ways in which the enabling environment facilitated impact drawing on perspectives of researchers, research users from government and UN agencies, and funders. We highlight three areas for funders to focus on strengthening enabling environments: (1) foster science-practitioner networks, (2) enhance collaborative research environments based on equitable partnerships, and (3) shift financing and incentives to sustain partnerships for impact at scale.